Sarcopenia influences clinical outcome in hospitalized patients with peripheral artery disease aged 75 years and older - Schmitt, Volker H.; Hobohm, Lukas; Brochhausen, Christoph; Espinola-Klein, Christine; Lurz, Philipp; Münzel, Thomas; Hahad, Omar; Keller, Karsten (Annals of vascular surgery, 2025)
Background - Sarcopenia represents a relevant comorbidity in patients with peripheral artery disease (PAD). However, only few studies exist assessing the clinical burden of sarcopenia in PAD. - Methods - All hospitalizations of patients aged ≥75 years who were admitted due to PAD within 2005-2020 in Germany were included in the study and stratified for sarcopenia. Temporal trends and the impact of sarcopenia on treatment procedures as well as adverse in-hospital events were investigated. - Results - Overall, 1,166,848 hospitalization cases of patients admitted due to PAD (median age 81.0 [78.0-85.0] years; 49.5% female sex) were included, of which 2,109 (0.2%) were coded with sarcopenia. Prevalence of sarcopenia in these patients increased during the observational period from 0.05% in 2005 to 0.34% in 2020 (β 2.61 [95%CI 2.42-2.80], P < 0.001). Sarcopenic PAD patients were more often female (52.1% vs. 49.5%, P = 0.015), obese (6.6% vs. 5.5%, P = 0.021), and revealed higher prevalences of comorbidities (Charlson comorbidity index, 7.00 [6.00-9.00] vs. 6.00 [5.00-7.00], P < 0.001). Sarcopenia was associated with reduced usage of reperfusion treatments (endovascular intervention: odds ratio (OR) 0.409 [95%CI 0.358-0.466], P < 0.001; surgical revascularization: OR 0.705 [95%CI 0.617-0.805], P < 0.001) but higher conduction of amputation (OR 1.365 [95%CI 1.231-1.514], P < 0.001) and higher rates of major adverse cardiovascular and cerebrovascular events (MACCE) (OR 1.313 [95%CI 1.141-1.512], P < 0.001) and in-hospital death (OR 1.229 [95%CI 1.052-1.436], P = 0.009). - Conclusions - Sarcopenia is an under-recognized condition in PAD patients of high clinical relevance causing a crucial disease burden. Awareness of the ailment needs to be increased in daily clinical practice to identify sarcopenia and improve the clinical outcome of this vulnerable patient group.